2017
DOI: 10.1016/j.epsl.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal vent complexes offshore Northeast Greenland: A potential role in driving the PETM

Abstract: Continental rifting is often associated with voluminous magmatism and perturbations in the Earth's climate. In this study, we use 2D seismic data from the northeast Greenland margin to document two Paleogene-aged sill complexes ≥18 000 and ≥10 000 km 2 in size. Intrusion of the sills resulted in the contact metamorphism of carbon-rich shales, producing thermogenic methane which was released via 52 newly discovered hydrothermal vent complexes, some of which reach up to 11 km in diameter. Mass balance calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 39 publications
0
55
0
Order By: Relevance
“…The magmatic hydrothermal systems were defined as aqueous fluid systems derived from or influenced by magma bodies (Ingebritsen et al, ; Pirajno & Van Kranendonk, ). They have been well studied at scales ranging from several kilometres to hundreds of kilometres in the mid‐ocean ridges, volcanic islands, passive margins and magmatic arcs along subduction zones, and play an important role in linking among the lithosphere, hydrosphere and biosphere (De Ronde et al, ; Gay et al, ; Hansen, ; Haymon, ; Ingebritsen et al, ; Lowell, ; Lowell & Germanovich, ; Medialdea et al, ; Planke, Rasmussen, Rey, & Myklebust, ; Reynolds et al, ; Wheeler et al, ). Consequently magmatically induced fluid flows may have a role in volcanically active regions such as the SCS.…”
Section: Introductionmentioning
confidence: 99%
“…The magmatic hydrothermal systems were defined as aqueous fluid systems derived from or influenced by magma bodies (Ingebritsen et al, ; Pirajno & Van Kranendonk, ). They have been well studied at scales ranging from several kilometres to hundreds of kilometres in the mid‐ocean ridges, volcanic islands, passive margins and magmatic arcs along subduction zones, and play an important role in linking among the lithosphere, hydrosphere and biosphere (De Ronde et al, ; Gay et al, ; Hansen, ; Haymon, ; Ingebritsen et al, ; Lowell, ; Lowell & Germanovich, ; Medialdea et al, ; Planke, Rasmussen, Rey, & Myklebust, ; Reynolds et al, ; Wheeler et al, ). Consequently magmatically induced fluid flows may have a role in volcanically active regions such as the SCS.…”
Section: Introductionmentioning
confidence: 99%
“…Generic models have shown that hydrothermal vent complexes arise from the expulsion of gases and fluidized materials associated with the emplacement of magmatic sills e.g., Svensen et al, 2006). During this process, substantial amount of gases are released to the atmosphere or hydrosphere e.g., (Aarnes et al, 2012;Jamtveit et al, 2004) and have been invoked as contributors to global warming during the Paleocene Eocene Thermal Maximum (PETM) (Reynolds et al, 2017;Svensen et al, 2004). Hydrothermal vents complexes usually originate from the tip of magmatic sill complexes as a result of intensive fracturing of the supra-sill stratigraphy arising from overpressure build-up associated with the release of fluids and gases within the metamorphic aureoles (Aarnes et al, 2012;Iyer et al, 2017;Jamtveit et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on the implication of hydrothermal venting for the timing of intrusive events e.g. (Hansen, 2006), petroleum systems (Aarnes et al, 2015;Iyer et al, 2017) and paleoclimate (Iyer et al, 2013;Iyer et al, 2017;Reynolds et al, 2017;Svensen et al, 2007;. However, there is a significant gap in our understanding of the interaction between the evolution of the hydrothermal vent complexes and deformation in the supra-sill stratigraphy.…”
Section: Introductionmentioning
confidence: 99%
“…[] and Reynolds et al . []. They act as a heat source that promotes organic matter maturation in their host rock and can trigger CH 4 and CO 2 ‐rich fluid production, releasing large amounts of carbon into the water column and the atmosphere through vent complexes [ Iyer et al ., ].…”
Section: Introductionmentioning
confidence: 99%